The effect of altruistic tendency on fairness in third-party punishment - Sun, Lu; Tan, Peishan; Cheng, You; Chen, Jingwei; Qu, Chen (Frontiers in Psychology, 2015)
Third-party punishment, as an altruistic behavior, was found to relate to inequity aversion in previous research. However, not all people show altruistic third party punishment, previous research found that altruistic tendency, as an individual difference, affects resource division. Here, using the ERP technique and a third party punishment of dictator game paradigm, we explored third-party punishments in high and low altruists and recorded their EEG data. Behavioral results showed high altruists (vs. low altruists) were more likely to punish the dictators in unfair offers. ERP results revealed that patterns of MFN were modulated by unfairness. For high altruists, high unfair offers (90:10) elicited a larger MFN than medium unfair offers (70:30) and fair offers (50:50). By contrast, for low altruists, fair offers elicited larger MFN while high unfair offers caused the minimal MFN. It is suggested that the altruistic tendency effect influences fairness consideration in the early stage of evaluation. Moreover, the results provide further neuroscience evidence for inequity aversion.